Effect of Porosity on Compressive Strength of Resin Modified Glass Ionomer Luting Cements - AHA, Al-Kadhim; H, Abdullah (IIUM Medical Journal Malaysia, 2020)
Introduction: The purpose of this study was to decide on the relation between types of mixing and the porosity of diameter (1-100) µm and compressive strength of RMGIC. Methods: Fifteen specimens 6mm height and 4mm in diameter were prepared for each type of luting cement and were stored in distilled water at 37° C for 24 hours. The compressive strength was determined. The fractured surfaces of 10 randomly selected specimens of each cement type were analyzed using SEM at 250 times magnification, and five photomicrographs were taken at five random places. All the photomicrographs were analyzed using image analyzer software to determine the amount and size of porosity present. Results: There was no significant difference in compressive strength between different mixing methods, but it had a significant impact by increasing the percentage of porosity of diameter (1-100) µm in diameter of RMGIC. There was no linear relationship between compressive strength and porosity (1-100) µm in diameter for both types of luting cements (P>0.05). Conclusion: No significant differences in compressive strength were found using different mixing methods. The size and number of porosity in the specimens of encapsulated cements were greater than those of hand-mixed cements. The porosity (1-100) µm in diameter and the compressive strength bore no linear relationship to each other.